Determinants of profitability in concept of going concern - Zarah Puspitaningtyas (Institute of Computer Science (IOCS), 2023)
Study aims to identify and analyze liquidity and financial leverage as determinants of profitability. Going concern is accounting assumption that expects business to continue indefinitely. This concept implies the company's responsibility to maintain stability and continuity comprehensively through its ability to earn profit from its operating activities. Real Estate and Property Companies listed in the KOMPAS 100 Index for period 2018 to 2022 as population, using purposive sampling technique, six companies were selected as samples. At significance level of 0.05, results of multiple linear regression analysis prove that liquidity has positive and significant effect on profitability, while financial leverage is not proven. These results imply that liquidity is determinant of profitability. Liquid companies will be seen as having high credibility and tend to cause positive reactions from investors, so that the company has sufficient capital to carry out its operational activities in effort to improve profitability to realize going concern concept